Ovarian Epithelial Cancer Stem Cells - Irena Conic; Irena Dimov; Desanka Tasic-Dimov; Biljana Djordjevic; Vladisav Stefanovic (The Scientific World Journal)
The last decade witnessed an explosion of interest in cancer stem cells (CSCs). The realization of epithelial ovarian cancer (EOC) as a CSC-related disease has the potential to change approaches in the treatment of this devastating disease dramatically. The etiology and early events in the progression of these carcinomas are among the least understood of all major human malignancies. Compared to the CSCs of other cancer types, the identification and study of EOC stem cells (EOCSCs) is rather difficult due to several major obstacles: the heterogeneity of tumors comprising EOCs, unknown cells of origin, and lack of knowledge considering the normal ovarian stem cells. This poses a major challenge for urgent development in this research field. This review summarizes and evaluates the current evidence for the existence of candidate normal ovarian epithelial stem cells as well as EOCSCs, emphasizing the requirement for a more definitive laboratory approach for the isolation, identification, and enrichment of EOCSCs. The present review also revisits the ongoing debate regarding other cells and tissues of origin of EOCs, and discusses early events in the pathogenesis of this disease. Finally, this review discusses the signaling pathways that are important regulators of candidate EOCSC maintenance and function, their potential role in the distinct pathogenesis of different EOC subtypes, as well as potential mechanisms and clinical relevance of EOCSC involvement in drug resistance.